Erythrocytic Reduced/Oxidized Glutathione and Serum Thiol/Disulfide Homeostasis in Patients with Opioid Use Disorder - Şahin, Esra Kabadayı; Senat, Almila; Söğüt, İbrahim; Duymaz, Tomris; Erel, Özcan (AVES, 2023)
Background: This study aimed to evaluate oxidative damage by measuring erythrocytic reduced/oxidized glutathione as an intracellular thiol pool and serum thiol/disulfide homeostasis as an extracellular thiol pool in patients with opioid use disorder. Methods: In this prospective cross-sectional study, 33 male patients diagnosed with opioid use disorder and 30 healthy male controls were included. Sociodemographic characteristics and psychometric analyzes were performed and addiction characteristics (duration and amount of heroin use, usage methods) were recorded. For the evaluation of oxidative balance, intracellular reduced-oxidized glutathione (reduced glutathione and oxidized glutathione), and extracellular thiol-disulfide (native thiol and disulfide) levels were measured. Results: There was a decrease in reduced glutathione and native thiol levels and an increase in GSSG and SS levels. Similarly, while oxidized/reduced glutathione, oxidized/total glutathione%, and disulfide/native thiol % ratios increased, the ratio of reduced glutathione/total glutathione% and native thiol/total thiol% decreased. Moreover, a positive correlation was found between the level of both intracellular and extracellular oxidant molecules and the duration and amount of opioid use. Conclusion: Impaired intracellular reduced glutathione/oxidized glutathione and extracellular disulfide/native thiol homeostasis were found in patients with opioid use disorder. The intracellular and extracellular oxidative stress may cause complications related to chronic opioid use.
Keywords: OXIDATIVE-STRESS; HEROIN; MORPHINEI; INVENTORY; ENZYMES